Tampilan jumlah anak sekelahiran, bobot badan dan ukuran tubuh saat lahir pada anak babi induk peranakan landrace - Yohanes Djego; Petrus Kune; Johny Nada Kihe (Universitas Nusa Cendana, 2021)
This aim of the research was to know production performances at birth age of piglets of landrace sow crossbreds. The research was carried out in two breeding farms namely the Instalation of Pig Breeding, village of Tarus, Kupang Regency and the Manise Pig Farm, Village of Oetete, Kupang City. There were 15 heads of landrace crossbreed sows. The method used wasa survey and samples were collected purposively that there were all of the landrace sow crossbreds. The variables were litter size, body weights, girth size, and body length. Data were differentiated between males and females. The data obtained was analysed using the t test (t-test). The results showed that males had the average of litter size, body weight, girth size and body length were 5.03±1.81 head; 1.48±0.58 kg/head; 24.82±3.29 cm and 22.21±4.18 cm, respectively while females had the average of liter size, body weight, girth size and body length were 4.80±1.49 head; 1.45±0.49 kg/head; 24.51±3.17cm and 21.78±4.75 cm, respectively. Statistical analysis showed that there was no difference (P>0.05) between males and females from all observation variables. Performances of piglets from ;andrace sow crossbreds for male and female characters such as litter size, birth weight, girth size and body length were relatively similar.